Wi-Fi Evolution: The Path Towards Wi-Fi 7 and Its Impact on IIoT - Frascolla, Valerio; Cavalcanti, Dave; Shah, Rahul (Journal of Mobile Multimedia, 2022)
This paper provides an overview of the Wi-Fi technology and its evolution along the years, touching on its inception and then elaborating more in details on the latest three commercial releases, linking the Wi-Fi advancements with the parallel cellular technology evolution towards 6G. Finally, a glimpse on the novelties proposed by the currently under definition Wi-Fi 7 release and more specifically on Wi-Fi sensing, a promising usage of Wi-Fi, are taken as an example of the forthcoming benefits of Wi-Fi in the smart home and Industrial Internet of Things (IIoT) domains.